Assistance of Nasyiah’s Business Group Passing through Branding and Digital Marketing to survive the pandemic - Nur Ravita Hanun; Hadiah Fitiyah; Muhammad Yani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Since Covid 19 burst into Indonesia, most of the Nasyiah members and their husbands have not been longer working due to termination of employment (PHK). Passing through discussions with the general chairman of PDNA Sidoarjo and the head of the socio-economic section of PDNA Sidoarjo, our community service team from the Muhammadiyah University of Sidoarjo has carried out several program activities, namely: through the Nasyiah business group, we increase the productivity of the economic activities of Nasyiah members who are not productive (unemployed) through various empowerments, namely product branding innovation, and digital marketing training. This public servant aims to increase the productivity of economic activities for unproductive (unemployed) Nasyiah members passing through various empowerments. These were launched into a situation analysis to formulate the right solution in overcoming the problems faced by partners. The empowerment was carried out through product branding training and digital marketing training. This community service program is able to improve community governance, human resources, and resource management. Partners already have product branding which are able to implement digital marketing strategies and are able to record business finances through the SME Accounting application created by the UMSIDA community service team